Understanding Racial/Ethnic Disparities in Physical Performance in Midlife Women: Findings From SWAN (Study of Women's Health Across the Nation). (14th August 2019) - Sternfeld, Barbara; Colvin, Alicia; Stewart, Andrea; Appelhans, Bradley M; Cauley, Jane A; Dugan, Sheila A; El Khoudary, Samar R; Greendale, Gail A; Strotmeyer, Elsa; Karvonen-Gutierrez, Carrie
Abstract: Objectives: Evaluate degree to which racial/ethnic differences in physical performance are mediated by sociodemographic, health, behavioral, and psychosocial factors. Methods: Physical performance was evaluated using a decile score derived from grip strength, timed 4 m walk, and timed repeat chair stand in 1, 855 African American, Caucasian, Chinese, Hispanic, and Japanese women, mean age = 61.8 ( SD = 2.7) in the Study of Women's Health Across the Nation. Mediators included education, financial strain, comorbidities, pain, body mass index (BMI), physical activity, and perceived stress. Structural equation models provided estimates of the total difference in physical performance between Caucasians and each race/ethnic groups and differences due to direct effects of race/ethnicity and indirect effects through mediators. Results: The mean decile score for Caucasian women was 16.9 ( SD = 5.6), 1.8, 2.6, and 2.1 points higher than the model-estimated scores in African Americans, Hispanics and Chinese, respectively, and 1.3 points lower than the Japanese. Differences between Caucasians and the Chinese and Japanese were direct effects of race/ethnicity whereas in African Americans and Hispanics 75% or more of that disparity was through mediators, particularly education, financial strain, BMI, physical activity, and pain. Discussion: Addressing issues of poverty, racial inequality, pain, and obesity could reduce some racial/ethnic disparity in functional limitations as women age.